MOMORDICA CHARANTIA - A POTENTIAL HEPATOPROTECTOR (International journal of medical sciences, 2026)
This article discusses the pharmacological properties of a plant widely used in folk medicine - Momordica charantia - also known as bitter melon, Indian pomegranate, etc. In our research, we studied the hepatoprotective properties of a dry extract of this plant in experimental hepatitis, using pharmacodynamic and biochemical research methods. It turned out that the studied substance has a strong hepatoprotective property and is in no way inferior to the famous hepatoprotective drug - Karsil, which can serve as a basis for creating a new hepatoprotective drug of plant origin.